Chronic Myeloid Leukemia: Part I—Real-World Treatment Patterns, Healthcare Resource Utilization, and Associated Costs in Later Lines of Therapy in the United States - Ehab L. Atallah; Rodrigo Maegawa; Dominick Latremouille-Viau; Carmine Rossi; Annie Guérin; Eric Q. Wu; Pallavi Patwardhan (Journal of Health Economics and Outcomes Research)
**Background:** Despite advances in tyrosine kinase inhibitor (TKI) therapy for chronic myeloid leukemia in chronic phase (CML-CP), a sizeable proportion of patients with CML-CP remains refractory or intolerant to these agents.